Community-Based Health Promotion and Its Influence on Hypertension Control among Elderly Populations - Ariyani Faradiza (Generasi Sains Indonesia, 2026)
This study aims to describe the effect of community-based health promotion in hypertension control in the elderly population in South Sulawesi, Indonesia. The research goal is to assess the influence of community health involvement on the control of blood pressure, drug adherence and lifestyle change among the elderly with hypertension. The design used was quantitative with cross sectional approach and the number of respondents was 300 elderly people participating in community health activities involving Posyandu Lansia and local health cadre. Structured questionnaires, medication adherence scales and direct blood pressure measurements were used to collect data which were analyzed descriptively, by Pearson correlation, multiple regression and analysis of variance. The results demonstrate that engagement in a community-based health promotion program has a significant impact on lowering BP, increasing adherence to medications and healthy lifestyle habits. Demographic and health factors were also controlled for, with community involvement being the strongest predictor of hypertension control. The novelty of the study is the incorporation of participatory governance and public health perspectives, conceptualizing community-based health promotion as a decentralised health management strategy, and not an educational intervention. The findings suggest that greater community involvement and culturally relevant health initiatives could help improve chronic hypertension control in the elderly in developing areas.